Identification of Hydatigera Species in Wildcats (Felis silvestris) from Central Spain - Matas-Méndez, Pablo; Esteban-Sánchez, Lorena; Ponce-Gordo, Francisco; Mateo-Barrientos, Marta (MDPI, 2025)
The European wildcat (Felis silvestris) is a mesocarnivore widely distributed across Europe, with populations in the Iberian Peninsula experiencing decline due to habitat fragmentation, hybridization with domestic cats, and anthropogenic factors. Among the parasites commonly found in wildcats are cestodes of the genus Hydatigera, which includes cryptic species within the Hydatigera taeniaeformis complex. This study aimed to identify Hydatigera species within this complex infecting wildcats in central Spain using both morphological and molecular methods. A total of 26 road-killed wildcats were collected between 2021 and 2023 from Castilla and León and Castilla-La Mancha. Cestodes were recovered from 73% of individuals, yielding a total of 240 Hydatigera specimens. Molecular analysis of the mitochondrial cox1 gene and a newly developed multiplex PCR targeting cox1, cytb and nad4 genes enabled differentiation between Hydatigera kamiyai and European Hydatigera sp., confirming their presence in definitive hosts in Spain for the first time. Mixed infections were detected in 60% of infected wildcats. The high prevalence and parasite load observed highlight the role of rodents in the transmission cycle. This study expands the known distribution of the H. taeniaeformis complex species in Europe and provides a reliable molecular tool for their identification, essential for further epidemiological investigations.